Systematic Sabotage in Educational Reforms: Analysing the JAMB Incident in the Context of CBT Expansion - Moses Adeleke Adeoye; Sabina Nwakaego Obi; Hakeem Nafiu; Kabir Olajide Soliu (Universitas Pendidikan Ganesha, 2025)
This research addresses the pressing issue of examination malpractice in Nigeria and its implications for implementing computer-based testing (CBT). The research investigates whether the recent technical failure of the Joint Admissions and Matriculation Board (JAMB) reflects systematic sabotage by stakeholders resistant to educational reform. This study employing a qualitative research design, the research utilizes a systematic literature review to analyses existing scholarship on trust, credibility, and economic motivations surrounding examination processes. The findings reveal that JAMB's failure has significantly eroded public confidence in examination bodies, creating skepticism that impedes the acceptance of CBT. Furthermore, entrenched economic interests, particularly those benefiting from traditional malpractice practices, actively resist changes threatening financial stability. The analysis emphasizes the need for a comprehensive approach to reform that addresses both technological and socio-economic dimensions. In conclusion, the research highlights that successful CBT implementation requires fostering stakeholder engagement, enhancing transparency, and addressing economic incentives linked to examination malpractice. The research contributes to the existing body of knowledge by providing a nuanced understanding of the interplay between technology, trust, and economic factors in educational reform. By identifying the challenges and proposing actionable recommendations, this research is a valuable resource for policymakers and education stakeholders seeking to navigate the complexities of implementing effective assessment practices in Nigeria.